Investigation of convection and radiation heat transfer of paraffinic materials and storage of thermal energy in melting process of PCMs in the cavity with transparent inner walls. (November 2022) - Javidan, M.; Asgari, M.; Gholinia, M.; Nozari, M.; Asgari, A.; Ganji, D.D.
Abstract: Phase change materials have wide applications as thermal energy storage systems. Due to the low thermal conductivity of these materials, lots of efforts have been made to increase the thermal conductivity and efficiency of thermal energy storage systems. In this numerical study, convective and radiation heat transfer on a cavity with transparent inner walls have been investigated considering the effects of buoyancy force and viscosity of phase change materials. For this purpose, computational fluid dynamics that have high accuracy in calculations have been used. The considered wall is made of brick, in which the cavity containing phase change materials is included and layers of cement and plaster are placed on the wall. The results indicate that increasing the heat flux increases the effects of convective heat transfer. In addition, by applying radiation effects, the melting process of paraffin materials increases by 31%. Due to the transparency of the inner walls of the cavity, the radiation process occurred surface to surface. Therefore, with increasing amount of molten material, the radiation effects increase, the reason for this is that RT24 material is more transparent in liquid form than solid material. Also, increasing the heat flux from 50 to 100 and 300 (w/m 2 ) increases the speed of the melting process by 19.3% and 27.2%, respectively. Graphical abstract: